2022
DOI: 10.3390/healthcare10020286
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy Student Perceptions of a Virtual Pharmacogenomics Activity

Abstract: Pharmacogenomics (PGx) utilizes a patient’s genome to guide drug treatment and dosing. The Accreditation Council for Pharmacy Education (ACPE) included PGx as a critical content area. Pharmacists are increasingly involved in providing this service, which necessitates training. Second-year pharmacy students at Samford University McWhorter School of Pharmacy have didactic training in the principles of PGx and managing drug therapy using PGx data. A clinical skills lab activity was developed to reinforce these pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Seven of the studies specifically surveyed students' opinions relating to in-person versus virtual skills-based labs [13,15,16,[18][19][20]23]. Three of the studies indicated that students felt less stressed during virtual lab simulations, while one study showed that although students had more time to prepare, most still felt an increase in stress levels during virtual skills-based lab simulations.…”
Section: Characteristics Of Selected Studiesmentioning
confidence: 99%
“…Seven of the studies specifically surveyed students' opinions relating to in-person versus virtual skills-based labs [13,15,16,[18][19][20]23]. Three of the studies indicated that students felt less stressed during virtual lab simulations, while one study showed that although students had more time to prepare, most still felt an increase in stress levels during virtual skills-based lab simulations.…”
Section: Characteristics Of Selected Studiesmentioning
confidence: 99%
“…5,6,15,16 With skills teaching and assessment, active learning, or team-based learning activities, student preference for learning varies, with recent literature noting in-person learning is preferred to virtual. 10,12,[17][18][19] Given the increased use of online learning and considering practices for professional development of future pharmacists, it is important to understand what knowledge, skills, and behaviors within the pharmacy curriculum can be taught online and assessed while also recognizing the challenges students may encounter in remote learning environments and offering strategies to overcome the potential negative impacts. This paper provides best practices for online learning and assessment in the didactic curriculum of pharmacy education and the potential implications on pharmacy student outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Many students noted a preference for a hybrid of online and in‐person teaching 5,6,15,16 . With skills teaching and assessment, active learning, or team‐based learning activities, student preference for learning varies, with recent literature noting in‐person learning is preferred to virtual 10,12,17–19 …”
Section: Introductionmentioning
confidence: 99%